Calculation of the centre of pressure on the athletic starting block - Ohshima, Y.; Bezodis, N. E.; Nagahara, R. (Sports Biomechanics, 2021)
We aimed to evaluate the accuracy of a new method to calculate the centre of pressure (COP) on a starting block above a force platform, and to examine how this method affected lower extremity joint torques during the block clearance phase compared against a previously used method which projects the COP from the metatarsophalangeal (MP) joint. To evaluate the accuracy of the new method, one experimenter applied force at 18 known locations on a starting block (under six block position and orientation conditions), during which ground reaction force was recorded underneath using a force platform. Two sprinters then performed three block starts each, and lower extremity joint torques were calculated during block clearance using the COP obtained from the new method and from the projection of the MP joint location. The calculated COP using the new method had a mean bias of =0.002 m. There were some large differences (effect sizes = 0.11-4.01) in the lower extremity joint torques between the two methods which could have important implications for understanding block clearance phase kinetics. The new method for obtaining the COP on a starting block is highly accurate and affects the calculation of joint torques during the block clearance phase.